RANTAI NILAI KLASTER INDUSTRI PENGOLAHAN SUSU DI DAERAH ISTIMEWA YOGYAKARTA - , Nur Laili Ma rufah, Prof. Dr. Ir. Tridjoko Wisnu Murti, DEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objectives of this study were to understand value chain of milk-cluster industry in the special region of Yogyakarta and analyze quality assurance of the dairy processors based on their performances in the implementation of GMPâs principle. Respondent and location were decided using purposive sampling method led to be analyzed descriptively. The results showed that stakeholders involved consist of dairy processors as core industry. Farmer, Livestock Farmer Groups (KTT), and cooperative as suppliers. In addition there are also found the role of related industries, supporting industries, buyers, and also supporting agencies or organizations. Pasteurized, fermented, and powdered milk reflects the product types made by dairy processors. Through the strategy of value chain approach and value chain mapping, it was obtained comprehensive information of the relationship (linkage) between stakeholders involved in milk-cluster industry as well as knowing the process of improving value in the chain (value adding production chain) in the cluster. Process in the value chain creates value in the field of labor, value-added industrial processes, value-added technological innovation, and economic value added. The concept of industrial clusters as for real could become a locomotive and accelerator for economic development in specific region. In connection with the implementation of GMP principles, most of the dairy industry (both cows and goats) have applied the principles of GMP.